A DEFENSE OF HUMEAN PROPERTY THEORY. (March 2021) - Lindsay, Ira K.
ABSTRACT: Two rival approaches to property rights dominate contemporary political philosophy: Lockean natural rights and egalitarian theories of distributive justice. This article defends a third approach, which can be traced to the work of David Hume. Unlike Lockean rights, Humean property rights are not grounded in pre-institutional moral entitlements. In contrast to the egalitarian approach, which begins with highly abstract principles of distributive justice, Humean theory starts with simple property conventions and shows how more complex institutions can be justified against a background of settled property rights. Property rights allow people to coordinate their use of scarce resources. For property rules to serve this function effectively, certain questions must be considered settled. Treating existing property entitlements as having prima facie validity facilitates cooperation between people who disagree about distributive justice. Lockean and egalitarian theories endorse moral claims that threaten to unsettle property conventions and undermine social cooperation.